Driving ethically towards an autonomous future - Baba, Tamana; Che Mustapha, Nurul Arfah; Hasbullah, Nurul Fadzlin (Kulliyyah of Engineering, IIUM, 2021)
Self-driving vehicles are expected to rise road safety, increase convenience, improve the mobility of those who are currently unable to use traditional vehicles, and reduce emissions. There are challenges, however, which may serve as obstacles on the path to an autonomous future. Some of them include technological and infrastructural challenges, vested interests, fear, perceived expense etc. In this paper, the self-driving revolution and its cascading effects have been explained. Various advantages as well the challenges faced in this matter and the ethical dilemmas faced in the smart automotive industry have been addressed.